Study on Stabilization of Soil Using Plant Roots and Lime (International Journal of Innovative Research in Engineering & Management, 2022)
Soil stabilisation is the process of modifying  soils in order to improve their physical qualities.  Stabilization can improve a soil's load bearing capacity to  support pavements and foundations by increasing its shear  strength and controlling its characteristics. Stabilization can  be used to remediate a variety of soil types, including  expansive clays and granular materials. A wide range of  additives, such as silica, lime, plant roots, fly-ash, and  cement, are used in this process. This project deals with  studying the stabilization of soils using plant roots and lime.  Samples were collected in this experiment from the Heerpora  area of Shopian (J&K) in the year 2021 with the aim to  quantify the effect of plant roots and lime on unconfined  compressive strength, california bearing ratio. The physical  and engineering qualities of the soil were determined through  experimental examinations. The material accessible at this  area was fine-grained dirt that was silty and clayey in nature.  The treatments consisted of five samples with lime and plant  roots (0%, 1.5% 3%, 5.0%, 7.0%). The unconfined  compressive strength showed an increase with the addition  then decrease the study found that optimum percentage of  lime and plant root is 3% of dry soil.
Keywords: Lime; Plant Roots; Soil samples; California Bearing Ratio; Cement; Fly Ash